Coronary artery disease in hypertension - Boruczkowska, Anna (Przewodnik Lekarza/Guide for GPs, 2006)
Arterial hypertension is one of the main risk factors in the development of coronary artery disease (CAD). Values of blood pressure in patients with CAD and arterial hypertension should be the same as in hypertonic patients without CAD. Great role in hypertension treatment of patients with CAD is played by nonfarmacological treatment. It lowers blood pressure and has a positive effect on other modificable risk factors in the development of CAD In farmacological treatment it is possible to use all groups of hypertension medications. In order to select a proper treatment we take into account the efficiency of a heart and any contraindications for using the preparation. In primary prevention of coronary artery disease for hypertonic patients is suggested to use angiotensin converting enzyme and calcium blockers. In secondary prevention we use β-blockers and angiotensin converting antagonism enzyme.